Ricerche sulla biodiversità delle comunità batteriche in tre laghi antartici - Michaud, Luigi; Lo Giudice, Angelina; Caruso, Consolazione; Mangano, Santina; Bruni, Vivia (Accademia Peloritana dei Pericolanti, 2009)
The bacterial diversity in three Antarctic lakes located at Crater Cirque (CC), Inexpressible Island (INI) and Luther Peak (LH) in the Victoria Land was investigated by a combination of culture-dependent and culture-independent techniques. The in situ abundance of different bacterial groups was determined by fluorescent in situ hybridization (FISH), while bacterial diversity among the cultivable microflora was investigated by culturing and genetic fingerprinting. Differences in the composition of bacterial assemblages were observed among the lakes investigated, when using the two approaches reported above. Overall, the detection rate by FISH of DAPI-stained cells varied from 48.4% to 68.9% with the general bacterial probe EUB338. Bacteria hybridizing with the group-specific probe CF319a were found to be abundant in the three lakes. A total of 478 strains were isolated from R2A agar plates and grouped by restriction analysis technique; sequencing of representative 16S rDNAs was performed to elucidate the taxonomic positions of isolates. Overall, isolates were placed within five different taxa: ?-Proteobacteria (39%), Bacteroidetes (35%), ?-Proteobacteria (8%), Actinobacteria (7%) and ?-Proteobacteria (5%). Finally, the 5.8% of total isolates shared the highest degree of sequence identity with unclassified bacteria. Members of the ?-Proteobacteria predominated at INI, whereas isolates from CC and LH mainly belonged to the Bacteroidetes. Among the ?-Proteobacteria, the genus Pseudomonas was predominant, whereas Flavobacterium spp. were very common among the Bacteroidetes. Finally, several Actinobacteria were closely related to unknown Antarctic bacteria.